2020
DOI: 10.1371/journal.pone.0240979
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between non-caries cervical lesions and the tooth and periodontal tissue: An ex-vivo study using micro-computed tomography

Abstract: The purpose of this study was to analyze the relationship between the height and depth of buccal non-carious cervical lesions (NCCLs) and the relationship between the size of buccal NCCLs and clinical crown-root ratio of both buccal and lingual (palatal) sides using micro-computed tomography (micro-CT) images of the teeth and periodontal tissues from the cadavers. The micro-CT images of 56 teeth and their supporting tissues were obtained from 17 cadavers. From these images, the height and depth of NCCLs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…The dental cracks can be understood as predecessors to the formation of NCCLs, and many researchers have reported an interrelationship between occlusal loads and stress and the development of NCCLs [12,30,33,48,[50][51][52]. Research by Donovan et al [53] indicated that excessive vertical occlusal loads are associated with the progression of all types of NCCLs.…”
Section: Discussionmentioning
confidence: 99%
“…The dental cracks can be understood as predecessors to the formation of NCCLs, and many researchers have reported an interrelationship between occlusal loads and stress and the development of NCCLs [12,30,33,48,[50][51][52]. Research by Donovan et al [53] indicated that excessive vertical occlusal loads are associated with the progression of all types of NCCLs.…”
Section: Discussionmentioning
confidence: 99%
“…In the specialized literature, there are studies on the morphology, etiology and evolution of NCCLs using various methods of investigation, among which we mention the following: the optical coherence tomography method (OCT) [20][21][22], micro-computed tomography [23,24], and electron microscope examination [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Com isso, dos fatores contribuintes com a etiologia, a fricção, de acordo com Lim et al (2020), pode ser dividida em um desgaste fisiológico resultante dos contatos dentários, denominado atrição ou em abrasão, conceituada como a frequente ação de esfregar os elementos dentais com componentes bucais e objetos que não sejam dentes.…”
Section: Introductionunclassified